STRUCTURAL EQUATION MODELING : DETERMINANT OF WORK MOTIVATION AND ITS IMPLICATION ON EMPLOYEE PERFORMANCE OF PT. JASA MARGA JAKARTA - Diniamalia Diniamalia; Alex Zami; R. Rudi Alhempi; R. Djoko Goenawan (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
This study aims to test and analyze the influence of Training, Organizational Culture, Perceived Organization Support (POS) and Work Motivation on the Performance of PT. Jasa Marga, Tbk, Jakarta's Implementing Employees - both partially and simultaneously. This study uses descriptive and quantitative methods through survey techniques. The research instrument uses a questionnaire with a Likert scale. Data analysis is processed using the SPSS version 24 program, and Structural Equation Modeling (SEM) with the Lisrel 8.72 program. The population is 7790 people while the sample is determined based on the Slovin formula of 220 people drawn through proportional random sampling techniques. The results of the study on Structure-1, prove: Training, Organizational Culture and POS simultaneously contribute 87% to the Work Motivation of PT. Jasa Marga, Tbk, Jakarta's Implementing Employees. Partially, POS has the most dominant influence with the dimensions that most reflect: Welfare Support and indicators: Concern for Environmental Conditions. While Organizational Culture has no significant effect. Structure 2, proves: Training, Organizational Culture, POS and Work Motivation simultaneously contribute 92% to the Performance of PT. Jasa Marga, Tbk, Jakarta's Implementing Employees. Partially, Training has the most dominant influence on Employee Performance, while Organizational Culture and POS are not proven to have an effect. The dimension that best reflects Training is: Training Participants with the indicator: Training is able to improve Employee Careers. Other important findings from the results of this study are: Work motivation only plays a role as a Partial Mediator for organizational culture and POS, while Training does not mediate.Keywords : Employee Performance, Work Motivation, Training, Organizational Culture, Perceived Organizational Support (POS).